Ultrasonication-promoted synthesis of luminescent sulfur nano-dots for cellular imaging applications. Issue 86 (14th October 2019) - Zhang, Chuanchuan; Zhang, Peng; Ji, Xiaojing; Wang, Henggang; Kuang, Haizhu; Cao, Weiling; Pan, Mingyue; Shi, Yu-e; Wang, Zhenguang
Abstract : An ultrasonication-promoted strategy was proposed to synthesize luminescent sulfur nanodots, reducing the synthesis time from 5 days to several hours. Abstract : An ultrasonication-promoted strategy was proposed to synthesize luminescent S-dots, which reduced the synthesis time from the commonly used 5 days to several hours. The as-synthesized S-dots show a high photostability and low cytotoxicity, and are then successfully applied for cellular imaging.